On the waveform fidelity of broadband digital storage architectures - Küsel, T.W (Department of Electrical Engineering, 2016)
Recent advances in digital technology resulted in the advent of high-density, very large-scale and very high-speed integrated circuit devices. For the first time it has become viable to store and/or process digitally sufficient lengths of very broadband signals. The digital capturing, storage and processing of a signal has some obvious advantages over traditional analogue methods. Given such a digital receiver technology, the system designer has at his disposal complete, real-time, receiver and processor reconfigurability. In this thesis, a number of architectures for the digital capture, storage and reconstruction of broadband signals are investigated. A comparison of these architectures is made, based on the fidelity of the reconstructed signal. Techniques for improving the quality of the reconstructed signal are also investigated. The results are aimed at aiding the system designer in choosing a receiver architecture for a specific system requirement.